Accumulation of 131Iodine in the nasolacrimal sac/duct after radioiodine therapy for papillary thyroid cancer - Usmani , Sharjeel; Jain, Anjali; Al Riyami, Khulood; Abubakar, Sofiullah (Journal of the Pakistan Medical Association, 2023)
SPECT/CT is a powerful tool for assessing unexpected concentrations of radioiodine resulting from benign uptake in organs with sodium-iodide symporter (NIS) expression. We report a case of accumulation of 131Iodine in the nasolacrimal sac/duct after radioiodine therapy for papillary thyroid cancer. A whole-body scan was taken 3 days after the administration of 5.5 GBq of 131Iodine. SPECT/CT images localized the focal tracer uptake in the nasolacrimal sac/duct likely due to nasolacrimal duct obstruction secondary to prior radioiodine or iodine therapies. Hybrid SPECT/CT allows precise anatomical localization and help differentiate benign mimics of disease, which can alter patient management. Keywords: 131Iodine SPECT-CT, thyroid cancer, papillary thyroid cancer, nasolacrimal duct obstruction